Malaria vector control in sub-Saharan Africa: complex tradeoffs to combat the growing threat of insecticide resistance - Oxborough, Richard M; Karen L Figueroa Chilito, Karen L Figueroa; Tokponnon, Tatchémè Filémon (My University, 2024)
Mass distribution of insecticide-treated nets (ITNs) has been a key factor in reducing malaria cases and deaths in sub-Saharan Africa. A shortcoming has been the over-reliance on pyrethroid insecticides, with more than 2·13 billion pyrethroid ITNs (PY ITNs) distributed in the past two decades, leading to widespread pyrethroid resistance. Progressive changes are occurring, with increased deployment of more effective pyrethroid-chlorfenapyr (PY-CFP) or pyrethroid-piperonyl butoxide (PY-PBO) ITNs in areas of pyrethroid resistance. In 2023, PY-PBO ITNs accounted for 58% of all ITNs shipped to sub-Saharan Africa. PY-PBO and PY-CFP ITNs are 30–37% more expensive than standard PY ITNs, equating to an additional US$132–159 million required per year in sub-Saharan Africa to fund the shift to more effective ITNs. Several countries are withdrawing or scaling back indoor residual spraying (IRS) programmes to cover the shortfall, which is reflected by the number of structures sprayed by the US President’s Malaria Initiative decreasing by 30% from 5·67 million (2021) to 3·96 million (2023). Benin, located in West Africa, is a prime example of a country that ceased IRS in 2021 after 14 years of annual spraying. Our economic evaluation indicates that IRS in Benin cost $3·50 per person protected per year, around five times more per person protected per year compared with PY-PBO ($0·73) or PY-CFP ITNs ($0·76). Although costly to implement, a major advantage of IRS is the portfolio of at least three chemical classes for prospective resistance management. With loss of synergy to PBO developing rapidly, there is the danger of over-reliance on PY-CFP ITNs. As gains in global malaria control continue to reverse each year, current WHO projections estimate that key 2030 malaria incidence milestones will be missed by a staggering 89%. This Personal View explores contemporary malaria vector control trends in sub-Saharan Africa and cost implications for improved disease control and resistance management.
Keywords: Malaria Vector; Sub-Saharan Africa; Complex trade-off; Cost implication; Threat Insecticides resistance